2013
DOI: 10.1128/aem.01657-13
|View full text |Cite
|
Sign up to set email alerts
|

An Extracellular Serine/Threonine-Rich Protein from Lactobacillus plantarum NCIMB 8826 Is a Novel Aggregation-Promoting Factor with Affinity to Mucin

Abstract: Autoaggregation in lactic acid bacteria is directly related to the production of certain extracellular proteins, notably, aggregation-promoting factors (APFs). Production of aggregation-promoting factors confers beneficial traits to probiotic-producing strains, contributing to their fitness for the intestinal environment. Furthermore, coaggregation with pathogens has been proposed to be a beneficial mechanism in probiotic lactic acid bacteria. This mechanism would limit attachment of the pathogen to the gut mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 49 publications
0
19
1
Order By: Relevance
“…These results were consistent with the inhibitory effects of an anti‐fibronectin antibody on the binding of LG2055 to Int407 cells (http://onlinelibrary.wiley.com/doi/10.1111/mmi.13153/suppinfo). A recent study demonstrated that APF from L. plantarum NCIMB 8826 shows affinity to mucin (Hevia et al ., ). Although GST‐APF1 showed weak binding to mucin, the binding showed a very fast dissociation curve (http://onlinelibrary.wiley.com/doi/10.1111/mmi.13153/suppinfo), suggesting that mucin might not be a major target molecule of LG2055 APF1.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These results were consistent with the inhibitory effects of an anti‐fibronectin antibody on the binding of LG2055 to Int407 cells (http://onlinelibrary.wiley.com/doi/10.1111/mmi.13153/suppinfo). A recent study demonstrated that APF from L. plantarum NCIMB 8826 shows affinity to mucin (Hevia et al ., ). Although GST‐APF1 showed weak binding to mucin, the binding showed a very fast dissociation curve (http://onlinelibrary.wiley.com/doi/10.1111/mmi.13153/suppinfo), suggesting that mucin might not be a major target molecule of LG2055 APF1.…”
Section: Resultsmentioning
confidence: 97%
“…APFs have also been shown to contribute to Lactobacillus acidophilus NCFM survival during passage through the GI tract by influencing tolerance to stress and interacting with the host intestinal mucosa as well as fibronectin, a major extracellular matrix component (ECM) (Goh and Klaenhammer, 2010). A serine/threonine-rich APF protein, which induces self-aggregation and has affinity to type III mucin, has been discovered in Lactobacillus plantarum NCIMB 8826 (Hevia et al, 2013). These data indicate that Lactobacillus APFs are closely involved in self-aggregation and/or adhesion to the host tissues in a strain-specific manner.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of biofilms with other species might be beneficial to the host as it may involve co‐aggregation with pathogens, thereby decreasing the colonization potential of the pathogens (Goh and Klaenhammer, ). Auto‐aggregation entails the aggregation of genetically identical cells, and can enhance the resistance to stress in the intestines (Hevia et al ., ). Aggregation promoting factors (APFs) are extracellular proteins, highly expressed in the stationary phase, that are directly linked to the ability to co‐aggregate (Boris et al ., ).…”
Section: Interaction With Other Microorganismsmentioning
confidence: 97%
“…Aggregation promoting factors (APFs) are extracellular proteins, highly expressed in the stationary phase, that are directly linked to the ability to co‐aggregate (Boris et al ., ). In L. plantarum NCIMB 8826, the serine/threonine domain of the APF, D1, binds to (porcine) mucin III and is involved in auto‐aggregation as it has been found that L. plantarum loses its auto‐aggregative abilities when gene D1 is knocked‐out (Hevia et al ., ). Moreover, gene D1 overproduction in L. lactis leads to aggregation.…”
Section: Interaction With Other Microorganismsmentioning
confidence: 97%
“…In this sense, the presence of encrypted peptides in larger extracellular proteins that may be released by the action of intestinal proteases interacting with the mucosal cells, and with a high proportion of serine and threonine amino acids, has recently been discovered. In L. plantarum, a serine/threonine rich protein (homologous to gi|28270057 from L. plantarum WCFS1) has been shown to promote cell aggregation (Hevia et al, 2013). A peptide of 6.8 kDa encoded within such protein, named STp, had regulatory effects on the human GIT through its interaction with human intestinal DCs, whose immune function was prone toward a tolerogenic response Al-Hassi et al, 2013).…”
Section: Extracellular Proteins and Encrypted Bioactive Peptidesmentioning
confidence: 99%